Energy conservation theory for second language acquisition (ECT-L2A): a partial validation of kinetic energy–aptitude and motivation - Kim, Peter (Frontiers in Physics, 2023)
While language aptitude and motivation are important contributors to second language (L2) attainment, two major gaps in the past research have been 1) a lack of non-linear models stemming from a naïve and tacit assumption that learning outcomes are linearly related to their predictors, and 2) a lack of unified and integrative understanding of key individual differences (ID) variables. This study aims to explore the relationship between motivation and aptitude in the context of second language acquisition using ideas from physics. This is done by seeking to validate several theoretical claims put forth by the energy conservation theory for second language acquisition (ECT-L2A) while attempting to integrate key ID variables into a unified model. In this study, 203 adult Spanish-speaking learners of L2 English were recruited. The participants encompassed a wide range of proficiency levels. To assess their language aptitude, the LLAMA_F test was administered, while motivation was measured using the Attitude Motivation Test Battery. Attainment was gauged through a grammaticality judgment test. Data analysis included correlation assessments, R-squared measures, and orthogonal regression employing the total least-squares method. The correlation analyses and regression findings were consistent with the predictions derived from ECT-L2A. Aptitude exhibited a positive relationship with attainment, but this effect diminished as proficiency increased. Conversely, while all participants displayed motivation to learn, motivation decreased as attainment levels advanced throughout L2 development. The effect of motivation on achievement followed an asymptotic pattern, with its contribution to target language (TL) mastery diminishing. Combining aptitude and motivation as a single unit, the learning trajectory mirrored the curve envisioned by ECT-L2A. The results of this study offer two key interpretations regarding motivation and aptitude in the context of second language acquisition. Firstly, both motivation and aptitude undergo changes in relation to attainment, with their effects varying as learners progress. Secondly, their efficacy in achieving native-like proficiency during L2 development differs significantly. These findings underscore the importance of considering the non-linear and interconnected nature of language aptitude and motivation in understanding their role in L2 acquisition. The implications of these findings for language teaching and learning strategies warrant further exploration.